(untitled) (Research, Society and Development, 2022)
Globally around 34 million children present disabling hearing loss. If unaddressed, hearing loss can negatively impact several aspects such as communication, cognition, language, and speech. Most needy people with hearing impairment do not have access to treatments and it’s a national and international public health problem. Meningococcal disease is caused by the bacterium Neisseria meningitides, affects mainly children, can cause hearing loss, and is a global public health challenge. This study aimed to present the case report of a child who acquired meningococcal disease and bilateral profound sensorineural hearing loss in primary infancy. At the age of six months, the child acquired meningococcal meningitis and performed antibiotic therapeutics. Four years later, the audiometric evaluation detected hearing loss. At the age of seven years, the patient started speech language therapy sessions. At the age of nine years, hearing prostheses were provided by a hospital. At the age of ten, the child began to deny the use of hearing aids at home and school. Two years later, she started her studies at a special school where the deaf community is clearly present. At the age of fourteen, the patient became completely fluent in Sign language, stopping speech therapy sessions. The analyzed case demonstrated a lack of children’s surveillance by a multidisciplinary team and the relevance of following children’s guidance vaccination. It is required to provide adequate interventions for children with hearing loss, which can potentially aid them to develop their skills and to achieve a better quality of life.